PANCASILA AND MANAGEMENT OF MONOPOLISTIC COMPETITIVE MARKET IN THE STUDY OF THE NATIONAL CRIMINAL CODE NUMBER: 1 OF 2023 AND CHINESE FOREIGNERS - Boro, Lorraine Rangga (Ridwan Institute, 2024)
In Indonesia, the National Criminal Code (KUHP) is based on the principles of Pancasila. This paper analyzes the legal and ethical frameworks guiding market practices in Indonesia, while examining the intersection of national legal standards and the influence of foreign participants in the economy. The research contributes to the understanding of how the integration of ideological values and legal regulations is integrated within the context of Indonesia's national Criminal Code Number 1 of 2023, particularly in relation to Chinese foreigners. This study provides insights into the legal, ethical, and economic practices guiding the management of monopolistic competitive markets in the study of the national criminal code number 1 in 2023 and China's foreign constitution. The analysis technique used is a qualitative approach that examines laws and regulations as reflections of Pancastila values, comparing them with Chinese foreign laws to understand how Pancasola principles can be applied to resolve monopoly cases. The study also examines whether the alignment of antitrust laws and economic democracy with Pancasilla leads to tangible improvements in market fairness and societal well-being. This research could provide insight into the practical implementation of ideologies in economic regulation and their impact on fostering a more equitable and transparent economic environment.